Influencia del conocimiento del resultado numérico en la resolución de problemas - Perales Palacios, F. Javier; Cervantes Madrid, A. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
In this paper an experimental study about a specific aspect of physics problem solving is carried out; namaless, the previous knowledge of their solution. Two groups of students attending the teachers' Training College of Granada were selected. Both groups were at random divided into two subgroups; one group knew the problem solutions before the experiment but the other one did not. The influence which the introduced variable exerts on the planning and solution of the problems, when the pupils are tested, has been statistically analyzed.